Analysis of the topics of sports talk shows on Iraqi satellite channels: The Captain’s Program in Al-Iraqiya Sports Channel as a model - Zaeid , Haider Falah; Saihood , Anmar Ghafil; Yusur , Marwan Khashlan; Yasir , Noor Kareem; Hassooni , Hussein Abdulameer (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this study was to identify the quality and nature of the topics raised in the sports talk programs of the Iraqi sports channel. With this purpose we analyzed how the channel deals with these topics and on what it focuses in The Captain’s Program in Al-Iraqiya Sports Channel. We also analyzed the hosted personalities in this program and their role in the sports community. In order to reach the objectives of the research, the survey method and the content analysis tool were used to analyze the episodes of the Captain program of the Iraqi sports channel, through intentional sample represented by a partial enumeration of the episodes of the mentioned program. In this paper we discussed the theoretical rooting of sports talk shows, their quality and importance in discussing the Iraqi sports reality, and a brief overview of the Iraqi sports channel and the Captain Sports talk show. In this study, we hope that we will shed light on knowing the most important topics discussed in the sports talk shows and come up with results that serve the communicator, the audience and the sports community.